An acoustic investigation of the rhythm of Yemeni Arabic and Jordanian Arabic / Nada Mohammed Abdo Salem - Salem, Nada Mohammed Abdo (2014)
In this study, the rhythm of Yemeni Arabic is measured and compared with Jordanian Arabic. The Arabic language has long been classified as being a stress-timed language. However, previous studies found that different Arabic dialects display different degrees of stress timing features forming a continuum that ranges from more stress-timed western Arabic dialects to less stress-timed eastern Arabic dialects. Yemeni Arabic is one of the Arabic dialects that has received little attention in terms of rhythm. Therefore, this study attempts to present an account of Yemeni rhythm based on the acoustic measures of its consonantal and vocalic durational intervals and compare them to those of Jordanian, which is one of the established and widely studied Arabic dialects. Recordings of Standard Arabic read speech and spontaneous Arabic speech of 10 Yemeni and Jordanian speakers were measured and analyzed using the Pairwise Variability Index (PVI) that calculates the durational variability in successive intervals. Based on the ideas posited by Dauer (1983), the measurements reflect certain phonological features, such as the syllable structure and vowel duration, that have an influence over the rhythmic structure of a language. The findings revealed that both Yemeni and Jordanian Arabic do not pattern differently in terms of the consonantal and vocalic intervals, thus, they seem to have comparable rhythmic structures. Interestingly, the two parameters used in this study resulted in two different classifications of rhythm types. That is to say, in terms of the consonantal durations, the PVI values of both Yemeni and Jordanian showed less durational variability indicating syllable-timed rhythm, whereas the PVI values of the Yemeni and Jordanian vocalic durations showed greater durational variability indicating stress-timed rhythm. The rhythm output of the speakers could be influenced by the mixed phonological features that these dialects display.